Amphibians from Santa Isabel do Rio Negro, Brazilian Amazonia - Menin, Marcelo; Carvalho, Vinicius Tadeu de; Almeida, Alexandre P.; Gordo, Marcelo; Oliveira, Deyla P.; Luiz, Luciana F.; Campos, Juliana V.; Hrbek, Tomas (Phyllomedusa: Journal of Herpetology, 2017)
A species list of amphibians from Santa Isabel do Rio Negro in Brazilian Amazonia is provided. Collections were made from March–April 2012 along each of two 3-km trails with the following sampling methods: (1) pitfall traps with drift fences; (2) visual and auditory surveys; and (3) chance encounters. The trail at Daraá is north of the Rio Negro, whereas the other in Ayuanã is south of the river. Forty species of anurans and one salamander species representing 20 genera and nine families were recorded. The species composition was compared with those of 16 other studies conducted in the Guiana, Imeri, and Jaú areas of endemism, where species richness varies from 21–63, and similarity indices range from 23–100%. The anuran fauna at our sites resembles that of Flota Faro in eastern Amazonia more than it does that of the nearest site in the Departamento del Guainía of Colombia. The index of similarity is extremely variable between sites of the same and distinct areas of endemism. This pattern also was observed in the cluster analysis. As expected, geographically close areas have similar faunal compositions. However, the anuran fauna of Parque Nacional do Jaú (Jaú area of endemism) resembles that of Manaus (Guiana area of endemism) more closely than it does that of the Ayuanã River, which belongs to the same area of endemism as Parque Nacional do Jaú. The limits of the areas of endemism are better defined by the presence / absence of other terrestrial vertebrates, such as birds and mammals, than by the assemblage of amphibians and squamate reptiles.